Comparative efficacy of citric acid, Spirulina platensis, and their combination as alternatives to an antibiotic growth promoter on the performances of broilers (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: A 35-day-long trial was conducted to compare the consequences of supplementing citric acid (CA), Spirulina platensis, and their combination as natural substitutes for antibiotic growth promoters (AGP) on the productive performance, dressing percentage, and blood serum metabolites of broilers.  Materials and Methods: A total of 150-day-old Cobb-500 broiler chicks were randomly assigned to 5 dietary treatment groups, each having 30 chicks in it (10 chicks per replicate cage). The dietary groups were as follows: 1- Control (corn–soybean-based), 2- Control + antibiotic (Enrofloxacin, 10 mg/kg bodyweight), 3- Control + 1% S. platensis, 4- Control + 0.5% CA, and 5- Control + 1% spirulina + 0.5% CA. Starting from day 7 up to day 21, antibiotics were administered via water; spirulina and CA were offered via feed.  Results: When compared to the control, all dietary supplements significantly (p < 0.05) improved broiler growth performance. However, dressing characteristics and serum metabolites (serum creatinine, albumin, and uric acid) were not influenced (p > 0.05) by dietary changes, except cholesterol level (p < 0.05). Supplementation with antibiotics, CA, and spirulina produced comparable results. Among them, the CA-fed group recorded the highest live weight, weight gain, feed intake, improved feed conversion ratio, and the lowest serum cholesterol level (106.5 mg/ dl). The combination group performed better than the control, but not as well as their single supplementations.  Conclusions: CA and S. platensis might both be good candidates as natural alternatives to AGP (Enrofloxacin). But, among them, CA performed better in terms of production performance.J. Adv. Vet. Anim. Res., 9(1): 1–7, March 2022http://doi.org/10.5455/javar.2022.i562